Aplikasi Canva Dan Kreativitas Desain Konten Instagram @Fisip Unsika Pada Mahasiswa Magang Fisip - Apriliyo, Tito Dwi; Abidin, Zainal (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Canva is a graphic design application or platform that is suitable for beginners who want to create or edit various types of designs online. The purpose of this study was to determine and measure the relative advantage, suitability, complexity, trialability, and visibility in the Canva application based on the theory used, namely the diffusion of innovation. This study uses a quantitative method with descriptive statistics and normality tests, simple regression analysis tests, partial tests (t), and determination coefficient tests (R2). The results of the study showed that there was a significant influence of relative advantage, suitability, complexity, and visibility, but no effect of trialability on the creativity of @fisipunsika Instagram content design on FISIP internship students.